Double Invisibility: Realising the Right to Vote for Persons with Intellectual Disabilities in Kenya - Kaburu, Valentine (Strathmore Law Review, 2024)
The right to vote is plausibly one of the most fundamental rights held by a citizen. It upholds the notion of equal citizenship and is intertwined with personal dignity. Historically, PWIDs have been denied their voting rights on the grounds that their disability impairs their ability to make rational decisions. The concept of making independent political judgments is fundamental to democracy; thus, if one is dependent on others to vote, they may become susceptible to undue influence or electoral fraud ultimately undermining the legitimacy of elections. Although reasonable, this perspective overlooks the unique demands of PWIDs who deserve an equal right to vote. The Constitution of Kenya recognises every citizen’s voting rights without unreasonable limitations. Despite this, PWIDs still encounter restrictions which stem from a lack of understanding of their unique demands. The imposition of blanket restrictions, such as those related to ‘unsound mind’, lack clear assessment criteria for voting purposes. This leads to uncertainty and misconceptions that PWIDs cannot make informed voting decisions. Through the relational personhood concept, this paper aims to demonstrate that PWIDs are not of unsound mind, but in the absence of good communication and require support to vote. It suggests the provision of reasonable accommodation to resolve the limitations encountered by PWIDs in Kenya.